Adolescent and Parent Preferences for Hypodontia: Discrete Choice Experiment. (December 2022) - Barber, S.; Bekker, H.; Marti, J.; Pavitt, S.; Khambay, B.; Meads, D.
Choosing hypodontia treatment requires young people and parents to consider a large amount of information, identify what is important to them, and make trade-offs between options. This study aimed to examine young people and parents' preferences for hypodontia treatment using discrete choice experiment (DCE). This was a cross-sectional survey of young people (12–16 y) with hypodontia of any severity, at any stage of treatment, and their parents. Participants were recruited from NHS Hospitals in England and Wales. A bespoke DCE questionnaire was developed to measure preferences for 6 attributes of hypodontia treatment (waiting time, treatment time, problems during treatment, discomfort during treatment, bite, appearance). The questionnaire was completed 1) online by young people and parents, individually or together, and 2) by child–parent dyads under observation. Preferences were analyzed using regression models. In total, 204 participants (122 young people, 56 parents, 26 dyads) completed the online questionnaire and 15 child–parent dyads completed the questionnaire under observation. The most important attribute in hypodontia treatment was improvement in appearance, but significant heterogeneity was found in preferences. Four distinct groups of participants were found: group 1 (39%): severe discomfort and problems were most important; group 2 (31%): most concerned about improvement in appearance of teeth and improvement in bite; group 3 (22%): appearance 3 times more important than any other attribute; and group 4 (9%): preferences difficult to interpret. There was variation in how child–parent dyads approached decision-making, with some negotiating joint preferences, while for others, one individual dominated. Making trade-offs in DCE tasks helped some people think about treatment and identify their preferences. Appearance is an important outcome from hypodontia treatment, but preferences vary and potential risks and functional outcome are also important to some people. There is a notable level of uncertainty in decision-making, which suggests further shared decision support would be valuable.